THE VIEWS OF PRE-SERVICE TEACHERS ABOUT TODAY AND FUTURE OF CURRENT WORLD PROBLEMS - Çağlar, Ayşe (International Online Journal of Education and Teaching, 2022)
This study aims to examine the opinions of social sciences pre-service teachers on the present and future of world problems. The study is a qualitative one and modeled according to the phenomenological research. The participants consist of pre-service teachers in the social sciences teaching undergraduates in Turkey. A survey that consists of open-ended questions developed by the researcher was used to collect the data. The data were analyzed using the qualitative descriptive analysis method. According to the research results, most of the participants stated that they were mostly concerned about human-based world problems. The world problem they are affected mainly by was women’s issues when they hear these problems from the news or experience these problems in their personal lives. Most of the pre-service teachers stated that education was the most important factor in solving the world problems and that women’s problems, which emerged as the most important problem, could also be solved by education. In their predictions for the future, they put forward that 50 years later, the world’s most important problem would be water scarcity, and most of the future problems would be related to nature.